2005
DOI: 10.1590/s1415-47572005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Multigene families encode the major enzymes of antioxidant metabolism in Eucalyptus grandis L

Abstract: Antioxidant metabolism protects cells from oxidative damage caused by reactive oxygen species (ROS). In plants, several enzymes act jointly to maintain redox homeostasis. Moreover, isoform diversity contributes to the fine tuning necessary for plant responses to both exogenous and endogenous signals influencing antioxidant metabolism. This study aimed to provide a comprehensive view of the major classes of antioxidant enzymes in the woody species Eucalyptus grandis. A careful survey of the FORESTs data bank re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…In fact, Papaver somniferum showed to possess at least eight different sequences, while Arabidopsis thaliana and Petroselinum crispum showed four different isoforms ( Table 1 ). The existence of two/three TDC isoforms in some plants may be aimed at more adequately responding to different exogenous and endogenous stimuli, as already reported for TDC gene [ 23 ], and for the antioxidant metabolism in Eucaliptus grandis [ 24 ]. Moreover, it is interesting to note that no TDC homologous is present in the genome of Arabidopsis thaliana .…”
Section: Resultsmentioning
confidence: 71%
“…In fact, Papaver somniferum showed to possess at least eight different sequences, while Arabidopsis thaliana and Petroselinum crispum showed four different isoforms ( Table 1 ). The existence of two/three TDC isoforms in some plants may be aimed at more adequately responding to different exogenous and endogenous stimuli, as already reported for TDC gene [ 23 ], and for the antioxidant metabolism in Eucaliptus grandis [ 24 ]. Moreover, it is interesting to note that no TDC homologous is present in the genome of Arabidopsis thaliana .…”
Section: Resultsmentioning
confidence: 71%
“…Two DHAR genes encoding for cytosolic and chloroplastic DHARs have also been identified in Eucalyptus spp. (Teixeira et al, 2005). DHAR also plays an important role in abiotic stress tolerance and its expression is activated by a number of abiotic stress factors (Ali et al, 2005;Lu et al, 2008;Fan et al, 2014).…”
Section: Dehydroascorbate Reductasementioning
confidence: 99%
“…At the molecular level, the specific sequences of distinct APX isogenes and their subfamily members have been recently identified in a variety of crop plants (Teixeira et al, 2004). The analysis of the phylogenetics and structural organization of APX genes has suggested that the different APX isoforms derive from a complex evolutionary process involving several gene duplications (Shigeoka et al, 2002;Teixeira et al, 2004Teixeira et al, , 2005. In rice, Teixeira et al (2006) reported that the members of the OsAPX gene family showed distinct transcript levels in response to NaCl and H 2 O 2 treatments, such as the elevated transcript for sAPX (stromal APX, OsAPX7) and the suppressed expression of tAPX isogene (OsAPX8) in rice under salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, three genes encoding GR isoform have also been identified in rice, including one cytosolic (OsGR2) (Kaminaka et al, 1998) and two chloroplastic isogenes (OsGR1 and OsGR3) (Trivedi et al, 2012). For OsMDHAR, this small gene family comprises five isoform members: two cytosolic isoforms (OsMDHAR1 and Os MDHAR2), two membrane-bound peroxisomal isoforms (OsMDHAR3 and OsMDHAR4), and one chloroplastic isoform (OsMD-HAR5) (Teixeira et al, 2005). DHAR enzymes are encoded by two isoform genes (OsDHAR1, and OsDHAR2) (Kim et al, 2013).…”
Section: Introductionmentioning
confidence: 99%